High-Skill Migration and Recession 2016
DOI: 10.1057/9781137467119_1
|View full text |Cite
|
Sign up to set email alerts
|

Female High-Skill Migration in the 21st Century: The Challenge of the Recession

Abstract: Anna Triandafyllidou 'When I was packing for Greece, I thought that my MBA from Harvard would allow me to easily find a good job in Athens, something like the chief executive officer or, at least, the project manager in a large firm'. Georgia, who is now 47, moved from Boston to Greece in the mid 1990s, following her Greek husband. Since then, she has been helping her father-inlaw with their family poultry business in a small Greek city, switching between the duties of their family-owned shop assistant and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…Hay diversas razones que pueden explicar la importancia de estos países como destinos de la emigración española. Los movimientos sur-norte de Europa están causados, además de por el desempleo en los países de origen, por las diferencias en las tasas de crecimiento entre países (Isaakyan y Triandafyllidou, 2016). La situación laboral de Alemania e Inglaterra es de las más positivas de Europa: en septiembre de 2017 la segunda y la cuarta tasas más bajas de desempleo en Europa se registraban en Alemania y Reino Unido (4% y 5% respectivamente), y Alemania presentaba la menor tasa de desempleo juvenil (Eurostat, 2017).…”
Section: Emigración Sur-norte De Europaunclassified
See 1 more Smart Citation
“…Hay diversas razones que pueden explicar la importancia de estos países como destinos de la emigración española. Los movimientos sur-norte de Europa están causados, además de por el desempleo en los países de origen, por las diferencias en las tasas de crecimiento entre países (Isaakyan y Triandafyllidou, 2016). La situación laboral de Alemania e Inglaterra es de las más positivas de Europa: en septiembre de 2017 la segunda y la cuarta tasas más bajas de desempleo en Europa se registraban en Alemania y Reino Unido (4% y 5% respectivamente), y Alemania presentaba la menor tasa de desempleo juvenil (Eurostat, 2017).…”
Section: Emigración Sur-norte De Europaunclassified
“…La cultura y el género como variables contextuales importantes en la adaptación a un nuevo contexto Las particularidades de la sociedad de origen y receptora determinan las características del proceso migratorio y la adaptación, haciendo que sea más o menos complicado en base a su origen cultural (Berry, 1997) y/o también a su género (Isaakyan y Triandafyllidou, 2016). Las personas con una mayor distancia cultural (real y/o percibida) respecto a la sociedad receptora se enfrentan a mayores dificultades socioeconómicas y culturales y a más situaciones de rechazo y discriminación (p.…”
Section: Adaptación E Integración Social Al País Receptorunclassified
“…Other expressions that erase the individual worker’s perspective are typically preferred, such as ‘circulation of human capital’, ‘knowledge exchange’ or ‘brain drain’ when the movement of skilled workers systematically impoverishes particular countries to the advantage of others, reflecting and amplifying global inequalities (Altbach, 2013; Blachford and Zhang, 2014; Nerdrum and Sarpebakken, 2006). Women can be doubly disadvantaged by their gender and outsider status when relocating, and highly skilled women are no exception (Isaakyan and Triandafyllidou, 2016). Seeber et al (2016) found that in the Flemish university system, men, native-born and internal candidates have better chances of getting hired than women, foreigner and mobile peers, and the effects are stronger for faculty positions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, the last decade has demonstrated an increasing demand for highly skilled professionals by territorial systems willing to increase their competitive positioning in the global economy, which has been described as a global “race for talent” (e.g., Frank et al., 2004; Shachar, 2006) or “research for the best and brightest” (e.g., Kapur & McHale, 2005; O’Leary et al., 2002). Many European countries have thus deployed skill‐selective labor immigration policies targeting workers in the science, technology, and engineering sectors (European Migration Network, 2007; Isaakyan & Triandafyllidou, 2016; Kofman, 2014).…”
Section: Introductionmentioning
confidence: 99%